Performance Optimization of Long-Haul Optical Transmission Link with Optical-OFDM - Deepak Kumar Singh, B. B. Tiwari, Jyoti Prashant Singh (International Journal of Intelligent Systems and Applications in Engineering, 2024)
This research focuses on improving communication system performance by implementing optical orthogonal frequency division multiplexing (OFDM). OFDM is utilized to extract data from high-capacity systems involved in extensive information transmission. Advanced computer programs and strategic methodologies are employed to develop a measurable and highly efficient communication system. The study delves into both theoretical and practical applications of these techniques. Using MATLAB simulations, the investigation into OFDM capabilities offers a robust platform for comprehensive analysis and evaluation. Researchers can easily adjust subcarrier separation, modulating schemes, and other key parameters to gauge their impact on system performance. This adaptability facilitates thorough exploration of various scenarios and optimization strategies. The findings of this study provide valuable insights into the effectiveness and feasibility of optical multiplexing with OFDM for high-capacity transmission in optical communication systems. Optical OFDM, through simulations, demonstrates outstanding spectrum utilization in the light domain compared to conventional radio-frequency (RF) OFDM, owing to its ability to tightly allocate subcarriers.